Construction of the identity and empowerment of the midwife during the practice of maternal health care in the Democratic Republic of the Congo - Kankolongo, Aline Mulunda; Ohambe, Marie-Claire Omanyondo; Bukasa, Augustin Kadiata; Leyka, Mukandu Basua Babintu (Orapuh Journal, 2024)
Introduction The professional identity of midwives develops and consolidates through various personal and professional experiences in the practice of care. However, the autonomous practice of midwifery, within a multidisciplinary approach, remains a significant obstacle to this construction. Purpose This study aims to understand how midwives construct their professional identity and autonomy in their practice. Method This is a qualitative study using grounded theory. Data were collected from seven midwives at the N’Djili General Reference Hospital through semi-structured interviews. The questions addressed professional identity. The analysis was conducted using open, axial, and selective coding, allowing the discovery of themes, categories, and concepts using an analysis grid. Results The construction of professional identity is associated with initial training, the specific care practices of midwives (roles), the support from health structures, and the support of the midwifery association. This process occurs through the practices of identity care, the precision of the midwife’s field of activities, the publication of professional guidelines, and the dissemination of regulations specifying the scope of action of midwives. Conclusion The midwifery profession has experienced significant evolution in its skills in recent years, an evolution perfectly integrated from academic training. It is, therefore, necessary to inform learners in training about ways to achieve professional autonomy in a clinical environment. Practicing midwives should strive to create autonomy within a professional group, practice and demand to perform autonomous acts, and provide independent care in maternity wards, birthing centers, medically assisted procreation centers, family planning centers, or in private practice when they are independent.